2009
DOI: 10.1111/j.1540-6261.2009.01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Investor Inattention and Friday Earnings Announcements

Abstract: Does limited attention among investors affect stock returns? We compare the response to earnings announcements on Friday, when investor inattention is more likely, to the response on other weekdays. If inattention influences stock prices, we should observe less immediate response and more drift for Friday announcements. Indeed, Friday announcements have a 15% lower immediate response and a 70% higher delayed response. A portfolio investing in differential Friday drift earns substantial abnormal returns. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
676
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,468 publications
(723 citation statements)
references
References 47 publications
42
676
1
4
Order By: Relevance
“…The earnings management effect dominates the bankruptcy avoidance effect for non-distressed firms. The results in Panel B are consistent with the findings of Dellavigna andPollet (2009) andMichaely, Thaler, andWomack (1995). Our results indicate that investors view distressed and non-distressed firms differently.…”
Section: Differences In the Sign Of The Responsesupporting
confidence: 87%
See 1 more Smart Citation
“…The earnings management effect dominates the bankruptcy avoidance effect for non-distressed firms. The results in Panel B are consistent with the findings of Dellavigna andPollet (2009) andMichaely, Thaler, andWomack (1995). Our results indicate that investors view distressed and non-distressed firms differently.…”
Section: Differences In the Sign Of The Responsesupporting
confidence: 87%
“…Therefore, the market reaction to an earnings surprise will be smaller for distressed firms than non-distressed firms, given an equal earnings surprise: Next we examine the difference in magnitude for positive and negative earnings surprises of distressed firms. Previous research has shown the price decrease associated with negative events to be larger in absolute terms than the price increase for positive information (Skinner & Sloan, 2002;Dellavigna & Pollet, 2009). One possible reason for this difference is the additional information associated with the firm's inability to meet analyst expectations.…”
Section: Investor Response To the Earnings Surprises Of Distressed Firmsmentioning
confidence: 97%
“…On an annualized basis, the returns we document are much larger than those generated by the postannouncement drift. (Doyle et al 2003), the price impact of Friday earnings releases (Dellavigna and Pollet 2009), observed investor over-optimism with respect to firms with high levels of net operating assets (Hirshleifer et al 2004), and the abnormally high levels of individual investor share purchases around the time of earnings announcements (Lee 1992;Barber and Odean 2008).…”
mentioning
confidence: 99%
“…This literature includes, among others, DellaVigna and Pollet (2009) and Hirshleifer, Lim, and Teoh (2009). These studies present evidence to suggest that mispricing (i.e., the post-earnings announcement drift) is more pronounced when traders are otherwise distracted, either because the weekend is imminent, or because there are a large number of announcements on the same day.…”
Section: Introductionmentioning
confidence: 95%